KORELASI ANTARA KEDISIPLINAN IBADAH SHALAT DENGAN AKHLAK SISWA : Volume 1, Nomor 1 (2024) - Mohammad Sobirin; Ratika Novianti; Nur Widiastuti (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2024)
Students’ prayer discipline is very high, this is proven by the results of the questionnaire which answered 52.78% inadequate, 27.78% adequate, and 19.44% good. The morals of students are good, this is proven by the report card data where 9 people got good marks, 12 people were good and 15 people were less. There is a significant correlation between prayer discipline and student morals. This can be seen from the 5% significance level obtained by "r" = 0.339, while at the 1% significance level obtained rtab = 0.436 or 0.339<0.96>0.436, meaning the Ha hypothesis is accepted while the Ho hypothesis is rejected (nil). And this relationship is classified as very high.